Reducing infectious complications after transrectal prostate needle biopsy using a disposable needle guide: is it possible? - Gurbuz,Cenk (2011)
PURPOSE: To investigate whether the use of a disposable needle guide results in a decreased incidence of infectious complication after transrectal prostate needle biopsy (TPNB). MATERIALS AND METHODS: Fifty five patients who underwent 10-core TPNB were randomized into two groups. A pre-biopsy blood and urine examination was performed in both groups. Group 1 (25 patients) underwent biopsy with disposable biopsy needle guide and Group 2 (30 patients) underwent biopsy with reusable biopsy needle guide. All patients had a blood and negative urine culture before the procedure. The patients received ciprofloxacin 500 mg twice a day beginning the day before the biopsy and continued for 3 days after. Serum C-reactive protein levels and urine and blood specimens were obtained 48h after the biopsy. Primary endpoint of the study was to determine the effect of needle guide on the bacteriologic urinary tract infection (UTI) rate and secondary end point was to determine symptomatic UTI. RESULTS: The mean age of the patients was 63.46 (range 55 to 68) years. There were no significant differences regarding the prostate-specific antigen level, prostate size, existence of comorbidity in two groups before the procedure. Bacteriologic and symptomatic UTI was detected in 4% vs. 6.6% and 4% vs. 3.9% in Group 1 and 2 relatively (P > 0.05). CONCLUSION: The use of a disposable needle guide does not appear to minimize infection risk after TPNB. Large scale and randomized studies are necessary to determine the effect of disposable needle guide on infection rate after TPNB.